Photocatalytic mineralization of carboxylic acids over Fe-loaded ZnS nanoparticles - Wetchakun N. (2014)
Zinc sulfide (ZnS) nanoparticles prepared by hydrothermal synthesis were subsequentially impregnated with different iron amounts (0.5-5.0 at%) to obtain Fe-loaded ZnS nanoparticles. Phase composition, crystallinity, crystal size, and morphology of 0.5-5.0 at% Fe-loaded ZnS nanoparticles were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDXS), X-ray photoelectron spectroscopy (XPS), and inductively coupled plasma (ICP). Specific surface area determined by the Brunauer, Emmett and Teller (BET) method was found to be in the range of 85-197 m2/g. The average particle size obtained from TEM analysis of pure ZnS and 2.0 at% Fe-loaded ZnS nanoparticles was 5-20 nm. The optical absorption properties of the samples measured by UV-vis diffuse reflectance spectroscopy (UV-vis DRS) clearly indicated the bathochromic shift upon loading ZnS with Fe. Photocatalytic activities of pure ZnS and Fe-loaded ZnS nanoparticles were examined by studying the mineralization of oxalic acid and formic acid under UVA illumination. It was found that 2.0 at% Fe-loaded ZnS sample exhibited the highest degradation activity possibly due to the presence of Fe in an optimum amount and the increases of surface area and light absorption in UVA region. © 2013 Elsevier Ltd.